Reurbanization and spatially polarized land markets: An analysis of urban land-value changes in North Rhine-Westphalia, Germany, 2012-2024; Reurbanisierung und räumlich polarisierte Bodenmärkte: Eine Analyse von Bodenpreisveränderungen in Nordrhein- Westfalen, Deutschland, 2012-2024 - Stefan Siedentop; Maximilian Schartmann (Raumforschung und Raumordnung / Spatial Research and Planning, 2025)
In recent years, land prices in Germany have skyrocketed to levels that were hardly thought possible. This has particularly affected prospering cities, where price increases of more than 100% have often been recorded since the turn of the millennium. The underlying causes are highly controversial. While some scholars point to the scarcity of developable land due to regulatory restrictions, others see the "financialization" of housing markets in the wake of the financial crisis and the massive influx of liquid capital into land and housing markets as the decisive driver. Against this background, this paper investigates the spatial patterns of land price dynamics in North Rhine-Westphalia during a phase of strong demographic and economic reurbanization. We used disaggregated data from the BORIS system for the years 2012 to 2024, which is available state-wide and georeferenced. Our empirical findings point to a significant trend of market polarization, with excessive growth rates in prospering metropolitan areas and real value losses in some rural areas. Overall, the paper offers new insights into the spatial patterns of urban land markets and possible driving factors explaining uneven developments. – – In den vergangenen Jahren sind die Bodenpreise in Deutschland in einer zuvor kaum vorstellbaren Weise gestiegen. Besonders betroffen sind prosperierende Großstädte, in denen sich die Preise seit der Jahrtausendwende häufig verdoppelt haben. Über die Hintergründe dieses Phänomens ist eine kontroverse Diskussion entstanden. Während einige Expertinnen und Experten auf die Knappheit an Bauland aufgrund von planerischen Restriktionen verweisen, halten andere Stimmen die "Finanzialisierung" der Wohnungsmärkte infolge der Finanzkrise und des Zustroms von anlagesuchendem Kapital für maßgeblich. Vor diesem Hintergrund untersucht dieser Beitrag die räumlichen Muster von Bodenpreisdynamiken in Nordrhein-Westfalen in der Phase einer starken demographischen und ökonomischen Reurbanisierung. Wir nutzen disaggregierte Daten des BORIS-Systems für die Jahre 2012 bis 2024, welche für das gesamte Land georeferenziert vorliegen. Unsere Ergebnisse zeigen einen signifikanten Trend einer Marktpolarisierung mit extrem starken Wachstumsraten in ökonomisch prosperierenden Stadtregionen und realen Wertverlusten in einigen ländlichen Gebieten. Unser Beitrag bietet einen neuen Einblick in die räumlichen Muster von Bodenmarktentwicklungen und mögliche Faktoren, die ungleiche Entwicklungen erklären können.
Keywords: 710; Land prices; Land market; Housing costs; Land use; Reurbanization; North Rhine-Westphalia; Germany; Bodenpreise; Bodenmarkt; Wohnkosten; Bodennutzung; Reurbanisierung; Nordrhein-Westfalen; Deutschland